Advances in sports food: Sports nutrition, food manufacture, opportunities and challenges. (July 2022) - Cui, Pengbo; Li, Mengyu; Yu, Mingxiao; Liu, Yefeng; Ding, Yuting; Liu, Weilin; Liu, Jianhua
Graphical abstract: Highlights: Nutritional components of sports food include basic nutrients and functional factors. Functional factors in sports foods play a very important role in regulating the physical functions of sportspeople. Sports food market contains sports drinks, solid and semi-solid sports food. The sports food industry has seen many opportunities and also faces some challenges. Abstract: In recent years, the increase in public awareness of sports has greatly promoted the development of the sports food industry. Sports food provides nutrition to meet the metabolic and energy needs of sports people. The nutritional components of sports food can be divided into basic nutrients and functional factors. Basic nutrients refer to the nutrients or metabolites required by the human body. Functional factors are bioactive ingredients that have potential effects in improving functions of the human body, such as protection of articular cartilage and improving muscle quality. Currently, there are various forms of sports foods in the market, including sports drinks, solid sports foods, semi-solid sports foods, and sports nutrition supplements. The sports food industry has seen many opportunities such as the expanding market, manufacturing technology development, and increasing funds investment. However, it also faces many challenges, such as lack of innovation, insufficient in-depth research, risks, and safety issues. This review would provide theoretical guidance for current sports food manufacture to meet the needs of increasing sports people worldwide.